Entrepreneurship Learning Process by using SWOT Analysis - Sudrajat, Jajat; Rahman, Muhammad Ali; Sianturi, Antonius; Vendy, Vendy (Bina Nusantara University, 2016)
The research objective was to produce a model of learning entrepreneurship by using SWOT analysis, which was currently being run with the concept of large classes and small classes. The benefits of this study was expected to be useful for the Binus Entrepreneurship Center (BEC) unit to create a map development learning entrepreneurship. Influences that would be generated by using SWOT Analysis were very wide as the benefits of the implementation of large classes and small classes for students and faculty. Participants of this study were Binus student of various majors who were taking courses EN001 and EN002. This study used research and development that examining the theoretical learning components of entrepreneurship education (teaching and learning dimension), where there were six dimensions of the survey which was a fundamental element in determining the framework of entrepreneurship education. Research finds that a strategy based on a matrix of factors is at least eight strategies for improving the learning process of entrepreneurship. From eight strategies are one of them strategies to increase collaboration BEC with family support. This strategy is supported by the survey results to the three majors who are following the EN001 and EN002, where more than 85% of the students are willing to do an aptitude test to determine the advantages and disadvantages of self-development and more of 54% of the students are not willing to accept the wishes of their parents because they do not correspond to his ideals. Based on the above results, it is suggested for further research, namely developing entrepreneurship research by analyzing other dimensions.